Post weld heat treatment of thermo-mechanical controlled process steel plates - Chin, Wan Ling (2014)
Thermo-mechanical controlled process (TMCP) steels have been developed to offer several inherent advantages due to its extremely fine-grained microstructure. The higher yield strength of TMCP steel is obtained through grain refinement and the effective reduction of the carbon alloy provides excellent weldability. TMCP Grade HBL 385 is widely used in Japan to create high strength, excellent earthquake resistant and yet easily weldable building frames. However, due to its recent introduction, there is little information regarding TMCP’s material properties after welding and relatively little is known concerning about the effects of PWHT upon both TMCP’s tensile strength and durability.